BREAST CANCER: A MODERN PROBLEM AND WAYS TO PREVENT IT - Rakhimova Shokhsanam Ikhvoljon kizi; Sherzodbek Nurmuhammad uglu (Web of Journals Publishing, 2025)
This article analyzes one of the pressing problems of modern medicine - breast cancer, its causes, risk factors and preventive measures. Based on statistical data, the prevalence of this disease and the threat to women's health are highlighted. It also considers ways to prevent breast cancer through early diagnosis, the role of screening programs, the formation of a healthy lifestyle and regular self-examination. The article also provides information on modern treatment methods - surgery, chemotherapy, radiation and hormonal therapy, and highlights the role of society and the healthcare system in overcoming the disease.
Keywords: Breast cancer, Oncological diseases, Women's health, Early diagnosis, Screening program, Prevention, Healthy lifestyle, Genetic factors, Chemotherapy, Radiotherapy, Hormonal therapy, Self-examination, Medical advice, Disease prevention, Health care system.